2021
DOI: 10.31004/prepotif.v5i2.2461
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Hubungan Perilaku Merokok dengan Obesitas Sentral Pada Orang Dewasa Sehat di Suradadi Kabupaten Tegal

Abstract: Central obesity is influenced by many factors such as changes in age, gender, economic status, life habits including lack of physical activity, low fiber consumption, consumption of simple carbohydrates, consumption of fatty foods, and smoking behavior. Smoking behavior is thought to be a significant factor in forming central obesity in adult males. The purpose of this study was to determine the relationship between smoking behavior and central obesity in healthy adults.  This study used an analytic observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
2
Order By: Relevance
“…Table 2 also shows the results that 86.4% of teenagers who do not smoke, do not experience overweight and obesity with a p value of 0.233 so persumably there is no correlation between adolescent smoking behavior and incidenceand obesity. The results of this study are in accordance with research conducted in Tegal which showed that no significant correlation was found between the relationship between smoking behavior and obesity 18 . In individuals who smoke, the nicotine in cigarettes can reduce the sensation of hunger 13 .…”
Section: Resultssupporting
confidence: 90%
“…Table 2 also shows the results that 86.4% of teenagers who do not smoke, do not experience overweight and obesity with a p value of 0.233 so persumably there is no correlation between adolescent smoking behavior and incidenceand obesity. The results of this study are in accordance with research conducted in Tegal which showed that no significant correlation was found between the relationship between smoking behavior and obesity 18 . In individuals who smoke, the nicotine in cigarettes can reduce the sensation of hunger 13 .…”
Section: Resultssupporting
confidence: 90%
“…Rokok merupakan salah satu faktor penyebab obesitas abdominal. Perokok memiliki risiko 1,3 kali lebih tinggi mengalami obesitas abdominal dibandingkan dengan bukan perokok (Susanto et al, 2021). Berbeda dengan rokok, kopi dapat mencegah obesitas abdominal.…”
Section: Pembahasanunclassified
“…Hal ini disebabkan dampak dari nikotin pada rokok yang dapat menurunkan nafsu makan. 27 Selain itu, adanya hubungan antara tidak merokok dan tidak mengonsumsi alkohol kemungkinan terjadi karena distribusi tidak seimbang pada sampel dalam desain cross-sectional dan terdapat faktor-faktor lain yang lebih dominan seperti pola makan dan aktivitas fisik. Model 4 dalam penelitian ini merupakan model terbaik dibandingkan model lainnya dikarenakan memiliki nilai koefisien determinasi (Negelkerke R square) paling besar dibandingkan model lainnya.…”
Section: Bahasanunclassified